Pemeriksaan Status Gizi dan Konsultasi Gizi sebagai Upaya Peningkatan Kesehatan Remaja - Ilmiyati, Liyana; Sahab, Novia Rahmah Maulani; Harjantini, Utami; Rafika, Muhana; Bonita, Ika Amalina; Rima A, Fatimah; Illahiyah, Putuhatul; Azizah, Hafidzah Nur (Yayasan Inspirasi El Burhani, 2025)
Introduction: Adolescence is a crucial period in the life cycle that requires special attention to nutrition and health. Adolescents in Islamic boarding schools are vulnerable to nutritional problems due to limited access to information and unbalanced eating habits. Objective: The purpose of this service was to increase adolescents’ awareness and knowledge regarding nutritional status and the importance of balanced nutrition through nutritional assessment and consultation. Method: The community service program was carried out at KHAS Kempek Islamic Boarding School with participants aged 13–18 years. The method included nutritional status assessment through weight, height, and mid-upper arm circumference measurements. Afterward, participants received individual nutrition counseling for 10–15 minutes focusing on balanced diet education. The activity was supported with educational media such as leaflets, food models, and questionnaires. Evaluation was conducted using pre–post tests and feedback to measure improvements in knowledge and awareness among adolescents. Result: The results indicated that most adolescents had a normal nutritional status. Nutrition consultations also contributed to increased awareness and knowledge about healthy and balanced eating. Conclusion: This activity demonstrated that educational and participatory approaches can support health promotion efforts among adolescents in boarding school settings.